Spatiotemporal response of dissolved organic matter diversity to natural and anthropogenic forces along the whole mainstream of the Yangtze River. (1st May 2023) - Li, Shuaidong; Meng, Lize; Zhao, Chu; Gu, Yu; Spencer, Robert G.M.; Álvarez–Salgado, Xosé Antón; Kellerman, Anne M.; McKenna, Amy M.; Huang, Tao; Yang, Hao; Huang, Changchun
Highlights: Allochthonous organics are the major sources for DOM pool in the Yangtze River. Natural conditions and anthropogenic forces modify riverine DOM chemo-diversities. Aromatic, unsaturated and humic-like DOM fractions dominate in up-midstream reaches. Seasonal phytoplankton growth produces labile aliphatic and protein-like compounds. Abstract: The Yangtze River, the largest river in Asia, plays a crucial role in linking continental and oceanic ecosystems. However, the impact of natural and anthropogenic disturbances on composition and transformation of dissolved organic matter (DOM) during long-distance transport and seasonal cycle is not fully understood. By using a combination of elemental, isotopic and optical techniques, as well as Fourier-transform ion cyclotron resonance mass spectrometry (FT-ICR MS), we investigated DOM abundance and composition along the whole mainstream at highly spatial resolution in the dry and early wet seasons. Our findings showed that the concentration and flux of dissolved organic carbon (DOC) in the Yangtze River was much lower compared with other worldwide larger rivers. The distribution of δ 13 CDOC and higher abundance of humic-like fluorescent component and highly unsaturated and phenolics (HUPs) compound reflected a prominent contribution of allochthonous DOM. Further optical and molecular analysis revealed humic-like fluorescent components were coupled with CHO molecules and HUPs compound with higher aromatic, unsaturated, molecular weight and stable characteristics between upstream and midstream reaches. With increasing agricultural and urban land downstream, there were more heteroatomic formulae and labile aliphatic and protein-like compounds which were derived from human activities and in situ primary production. Meanwhile, DOM gradually accumulates with slow water flow and additional autochthonous organics. Weaker solar radiation and water dilution during the dry/cold season favours highly aromatic, unsaturated and oxygenated DOM compositions. Conversely, higher discharge during the wet/warm season diluted the terrestrial DOM, but warm temperatures could promote phytoplankton growth that releases labile aliphatic and protein-like DOM. Besides, chemical sulfurization, hydrogenation and oxygenation were found during molecular cycling processes. Our research emphasizes the active response of riverine DOM to natural and anthropogenic controls, and provides a valuable preliminary background to better understand the biogeochemical cycling of DOM in a larger river. Graphical abstract: Highlighted characteristics and compositions of riverine DOM pool of three reaches and two seasons. Image, graphical abstract